2019
DOI: 10.13057/biodiv/d200511
|View full text |Cite
|
Sign up to set email alerts
|

Growth parameter, mortality, recruitment pattern, and exploitation rate of white shrimp Penaeus indicus in northern coastal waters of Western Central Java, Indonesia

Abstract: Abstract. Saputra SW, Solichin A, Taufani WT, Rudiyanti S, Widyorini N. 2019. Growth parameter, mortality, recruitment pattern, and exploitation rate of white shrimp Penaeus indicus on the northern coast of Central Java, Indonesia. Biodiversitas 20: 1318-1324. The aims of this study were to know the growth parameters, first lenght captured (Lc), mortality, recruitment pattern, and the exploitation rate of white shrimp (Penaeus indicus H.Milne Edwards, 1837) in the Western Coastal North Central Java Sea, Indone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Studies had shown that E max as the biological reference standard might lead to overly optimistic assessments, while E 10 and 0.5 standards could balance the current catches and reasonable utilisation (Gulland and Oerema, 1973;Cook, 1998). The biological reference points E 10 or 0.5 had been adopted in other species such as Penaeus indicus (Saputra et al, 2019) and Penaeus merguensis (Saputra et al, 2018). The exploitation rates of female and male swimming crabs calculated in this study were 0.61and 0.62, respectively, which were higher than the optimal rates of E 10 and 0.5, but close to the E max .…”
Section: Discussionmentioning
confidence: 99%
“…Studies had shown that E max as the biological reference standard might lead to overly optimistic assessments, while E 10 and 0.5 standards could balance the current catches and reasonable utilisation (Gulland and Oerema, 1973;Cook, 1998). The biological reference points E 10 or 0.5 had been adopted in other species such as Penaeus indicus (Saputra et al, 2019) and Penaeus merguensis (Saputra et al, 2018). The exploitation rates of female and male swimming crabs calculated in this study were 0.61and 0.62, respectively, which were higher than the optimal rates of E 10 and 0.5, but close to the E max .…”
Section: Discussionmentioning
confidence: 99%
“…When viewed as a whole, there were two peaks of recruitment, namely in May and June at 18.92% and 18.33% respectively after four months of white shrimp spawning. [14] state condition will also lead to the depletion of shrimp parent stock, which automatically will result in a decrease in recruitment. This means that it will cause a decrease in stock which eventually will result in a decline in capture result per trip (CPUE).…”
Section: Discussionmentioning
confidence: 99%
“…Possible factors affecting the allometry growth including the physiological condition and environmental factors such as pH, salinity, seasonal variation, sex ratio, temperature, geographical locations and sampling technique (Anand et al 2014;Udoinyang et al 2016;Putra et al 2018). Other studies also reported the negative allometry growth of white shrimps in Egypt (Elganainy 2012), Persian Gulf (Momeni et al 2018), West Java (Saputra et al 2019). The relationship between carapace length and body mass of white shrimp is presented in Figure 5.…”
Section: Growth Pattern Of White Shrimpmentioning
confidence: 97%